Time Well Spent: Exploring the Role of Attitude and Topic Importance on Selective Exposure to Agricultural Messages - Skylar Elmore; Courtney Meyers; Laura Morgan Fischer; Scott Burris; Amber McCord (Journal of Applied Communications, 2023)
New digital technologies, such as Web 3.0 and algorithms, allow social media users to customize their feeds, creating their own information bubble, which tends to align with prior beliefs and/or attitude. This action of seeking information that emphasizes or confirms pre-existing beliefs is called confirmation bias, which is often expressed through selective exposure. Although previous studies have explored selective exposure in the context of political and health communications, limited research has been completed related to this phenomenon in agricultural communications. Therefore, the purpose of this study was to explore the effects of attitude and topic importance on selective exposure to different agricultural messages. Using a quasi-experimental design, this study used a Qualtrics questionnaire to collect data from undergraduate students in a laboratory setting. Participants provided their attitudes and topic important for two agricultural issues. A fictional Twitter feed was created that linked to four blog posts that served as the message stimuli. To determine selective exposure, we recorded how many blog posts they selected and how long they spent on each message. The results indicated that participants had varying attitudes of the two agricultural topics but had equal views of importance. No significant difference in time spent on the messages on was found. The results indicated that the process of selective exposure is a complex construct that involves many factors. Additional research in this area will help agricultural communicators develop more effective message strategies and understand the role of confirmation bias in information processing.
Keywords: selective exposure; confirmation bias; attitude; topic importance; climate change; antibiotic use in livestock